Putting Consumer Experience Back into Consumer Research: The Philosophy and Method of Existential-Phenomenology - Thompson, Craig J.; Locander, William B.; Pollio, Howard R. (Journal of Consumer Research, 1989)
Existential-phenomenology is presented as an alternative paradigm for conceptualizing and studying consumer experience. Basic theoretical tenets of existential-phenomenology are contrasted with more traditional assumptions and methods used in consumer research. The metaphors used by each paradigm to describe its world view are provided and their respective implications for consumer research discussed. One phenomenological research method is detailed, and examples of how the method is applied and the type of data it produces are provided. An epistemological analysis reveals that existential-phenomenology can provide an empirically based and methodologically rigorous understanding of consumer phenomena.